Harnessing synthetic biology for mushroom farming. Issue 4 (April 2023) - Zou, Gen; Nielsen, Jens B.; Wei, Yongjun
Abstract: Recent advances in synthetic biology have transformed mushroom farming from a focus on traditional cultivation to comprehensive applications based on cutting-edge biotechnologies. Synthetic biology has promising applications in this field, including precision breeding, mining biosynthetic gene clusters, developing mushroom chassis cells, and constructing cell factories for high value-added products.